Ajwa Date (Phoenix dactylifera L.) Extract to Prevent Alzheimer’s Disease in Rat Model - Rizka Muthia Nuruddin; Brian Wasita; Adi Magna Patriadi Nuhriawangsa (Faculty of Medicine, Universitas Padjadjaran, 2023)
Alzheimer's disease (AD) is the most common disease of aging characterized by increased extracellular deposits of amyloid-β (Aβ) in the brain. Globally, the number of people affected by AD has increased from 35.6 million in 2010 to 46.8 million in 2015. Ajwa dates contain phenolic compounds that can protect against inflammation and oxidative stress in the brain. This study aimed to analyze the effect of the dose and duration of Ajwa date extract administration on IL-6 levels and SOD activity in rats induced with 400 mg/day homocysteine to trigger Alzheimer's Disease. This was a laboratory experimental study with a pretest-posttest group design conducted at the Laboratory of the Center for Food and Nutrition Studies (PSPG), Universitas Gadjah Mada, Yogyakarta, Indonesia from December 2020 - January 2021. A total of 48 rats were divided into one control group, one untreated group, and 4 treatment groups that received different doses of Ajwa Date Extract (ADE) for 21 and 28 days in rats. The results showed that the administration of ADE (Ajwa date extract) for 21 and 28 days could reduce IL-6 levels but did not have the same effectiveness as donepezil. The administration of 800 mg/kg BW ADE for 28 days can increase SOD activities with the same effectiveness as donepezil. Ajwa date extract can be proven to have beneficial effects to prevent Alzheimer's disease and can be used to prevent decreased antioxidant and increased inflammation. Thus, further studies to explore the potential clinical use of the extract to manage Alzheimer's Disease may be beneficial.